2013
DOI: 10.11622/smedj.2013173
|View full text |Cite
|
Sign up to set email alerts
|

Use of strong opioids for chronic non-cancer pain: a retrospective analysis at a pain centre in Singapore

Abstract: INTRODUCTIONThe use of opioids in chronic non-cancer pain (CNCP) is controversial, as it presents both benefits and risks. There is currently no available data on the incidence, prescription pattern, functional outcomes and adverse effects of opioids in patients with CNCP in Singapore. This study aimed to address the aforementioned deficit. METHODSAll records of patients who were prescribed strong opioids (for > 3 months per year) for the management of CNCP over a two-year period were retrospectively analysed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Offences involving PDs (e.g., nimetazapam) also face similar legal consequences as illegal drugs. A study conducted locally among those with chronic non-cancer pain has indicated methadone (45.2%), morphine (38.1%), oxycodone (23.8%) and fentanyl (9.5%) being the most prescribed pain medications [ 21 ]. Prescription opioids such as buprenorphine are highly discouraged in Singapore following a rapid increase in buprenorphine-related deaths in 2006 [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Offences involving PDs (e.g., nimetazapam) also face similar legal consequences as illegal drugs. A study conducted locally among those with chronic non-cancer pain has indicated methadone (45.2%), morphine (38.1%), oxycodone (23.8%) and fentanyl (9.5%) being the most prescribed pain medications [ 21 ]. Prescription opioids such as buprenorphine are highly discouraged in Singapore following a rapid increase in buprenorphine-related deaths in 2006 [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…33 In Singapore, one study reported that 3% of chronic pain patients received strong opioids for at least three months. 34 The study noted several key findings. First, improved function was demonstrated in 61.9% of the patients.…”
Section: Original Investigationmentioning
confidence: 92%
“…Third, 11.6% of this group ultimately demonstrated aberrancy. 34 In a similar study out of Japan, physicians reported that strong opioids showed clinical effectiveness in 77.3% of patients, opioid therapeutic goals were reached in 64.5% of patients, and 0.6% of patients experienced drug dependence. 35 In both studies, strong opioids were used on patients that were not responsive to other treatments.…”
Section: Original Investigationmentioning
confidence: 95%
See 2 more Smart Citations